Dihydromyricetin: an emerging compound with comprehensive effects on multiple systems - He, Chengyi; Chen, Yunfei; Xie, Jiao; Luo, Miao; Fisher, David; Hien, Nguyen Thi Thu; Musabaev, Erkin; Dang, Yiping; Zhao, Lei; Xia, Yin (Frontiers in Pharmacology, 2025)
Dihydromyricetin (DHM or DMY) is a flavonoid derived from natural sources with a range of confirmed biological benefits. It exhibits anti-inflammatory, antioxidant, anti-tumor, and anti-viral activities. DHM is recognized for its high biosafety, making it a promising subject for further research. This article offers a comprehensive overview of DHM’s pharmacological properties, mechanisms, and recent research developments in the cardiovascular, urinary, digestive, nervous, and respiratory systems. The review summarizes DHM’s biological effects and associated signaling pathways, providing novel insights for its clinical application.